A blueprint for national assessments of the blue carbon capacity of kelp forests applied to Canada’s coastline - Jennifer McHenry; Daniel K. Okamoto; Karen Filbee-Dexter; Kira A. Krumhansl; Kathleen A. MacGregor; Margot Hessing-Lewis; Brian Timmer; Philippe Archambault; Claire M. Attridge; Delphine Cottier; Maycira Costa; Matthew Csordas; et al. (npj Ocean Sustainability)
Abstract Kelp forests offer substantial carbon fixation, with the potential to contribute to natural climate solutions (NCS). However, to be included in national NCS inventories, governments must first quantify the kelp-derived carbon stocks and fluxes leading to carbon sequestration. Here, we present a blueprint for assessing the national blue carbon capacity of kelp forests in which data synthesis and Bayesian hierarchical modeling enable estimates of kelp carbon production, storage, and export capacity from limited data. Applying this blueprint to Canada’s extensive coastline, we estimate kelps hold 0.6 to 2.8 Tg C in short-term biomass, producing 1.1 to 6.2 Tg C yr-1, of which 0.04 to 0.4 Tg C yr-1 could be exported to the deep ocean. While modest compared to terrestrial sinks, our findings suggest kelps have comparable carbon sequestration to marine and freshwater wetlands, warranting further consideration in Canada’s NCS inventories. Our transparent, reproducible blueprint represents an important step towards accurate carbon accounting for kelp forests.